Urban health inequality in shifting environment: systematic review on the impact of gentrification on residents' health - Delong, Sun (Frontiers in Public Health, 2023)
The impacts of changing neighborhoods, and the influence of neighborhood stability on residents' health have not received enough attention in the literature; one of the most important aspects is gentrification. Research on the impact of gentrification on residents' health has gradually increased in recent years, mainly from North America. Based on the guidelines of PRISMA 2020 and SCIE, 66 papers were included for analysis, six aspects of selected studies are discussed: the research design, theoretical framework, methods of analysis, definition and measurement of gentrification effects, and impact pathways. In general, most of the literature in this field can be seen as using an ecological research design, of which cross-sectional research accounts for a large proportion. The identified effects vary in their direction as well as strength due to difference in population, temporal, and geographical characteristics. Gentrification could affect health outcomes through the combination of economic, social, and physical environment factors. Existing research could be improved in the following aspects: (1) The definition and measurement of gentrification should be both generic and site-specific; Various measurement methods should be compared to enhance the robustness of the results. Furthermore, more consideration should be given to the impact of spatial issues; (2) As for health outcomes, it is suggested to expand the scope of the discussion of health outcomes and strengthen the biological explanation of the influencing mechanisms. It is also necessary to determine the research time points according to the characteristics of the incubation period of different diseases; (3) As for research design, applying longitudinal research design is more likely to improve the reliability; (4) Theoretical frameworks should be addressed to link the definition and measurement of gentrification, patterns of health outcomes, methodology and pathways.